If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -70 + 60 = 0 Reorder the terms: -70 + 60 + 4x = 0 Combine like terms: -70 + 60 = -10 -10 + 4x = 0 Solving -10 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 4x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = 0 + 10 4x = 0 + 10 Combine like terms: 0 + 10 = 10 4x = 10 Divide each side by '4'. x = 2.5 Simplifying x = 2.5
| 0.4(8-0.2)=4 | | 3z=12 | | 2z^2+2iz+x=0 | | AB=BA | | 2(x+2)+x+2=21 | | 145l+36=433 | | 12g-3=30 | | 9x-23=3x-1 | | (x-10)(3x+12)=3x-900 | | -8+8g=0 | | 10x^2+x-20=0 | | (x-10)(3x+12)= | | 6m-4m+3=11 | | x^2-16x-3=0 | | 2z^2+2iz-5=0 | | z^2+2iz-5=0 | | 4-3=21 | | 22p+7p^2=-3 | | 6(x+2)=5(x-y) | | -3y-7=20 | | -8=7y+12 | | y=-9(-1)-1 | | -10=-9x-1 | | x+2(3)=4 | | 15x=5x-20 | | 1=.5(x) | | .5(-12)= | | 4=2-x | | 12n+3n=-18 | | -(-1)-4= | | X(y-2)=y+1 | | y=-0-4 |